The Other as Brother: Nation-Building and Ethnic Ambivalence in Early Jewish-Israeli Anthropology - Goodman, Yehuda; Loss, Joseph (Anthropological quarterly, 2009)
Most depictions of "peripheral," nation-states' anthropologies assume that the anthropology's Other is a given, pre-defined subordinated group. Using the beginnings of Israeli anthropology (1960s-1970s) as our case study, we explore instead how while appropriating academic dominant paradigms of the time and aspiring to national unity, Israeli anthropologists were articulating through their choices of research subjects and research topics, and through their interpretations of the field an ethnic difference between themselves, European Jews and their "brothers," Oriental Jews. We follow the ambivalent discursive strategies through which this research project was created, and explore its implications for understanding other nation-building anthropologies.